Manajemen Krisis dalam Kebijakan Fiskal: Analisis Komentar Youtube Terhadap Wacana Pemotongan Anggaran ASN - Novi Satria Jatmiko; Mardatillah (Nusantara Innovation Journal, 2025)
This study analyzes public opinion regarding the State Civil Apparatus (ASN) budget reduction policy in the Prabowo administration. This study uses a qualitative content analysis method by examining comments on the YouTube video “ASN Will Suffer If Many Budgets Are Cut in the Prabowo Administration” using NVivo 12 Pro software. The results of the study show that the majority of comments have negative sentiments. The main concerns include ASN welfare, economic stability, and the decline in the quality of public services. The public also demands transparency and fairness in policies, pushing for budget reduction not only to ASN but also high-ranking officials and the DPR. This study confirms that social media, especially YouTube, plays a role as an advocacy space that shapes public perception of fiscal policy. Therefore, a more transparent, data-based, and participatory crisis management strategy is needed to reduce public resistance to controversial policies.